Home Environmental Conditions With Dengue Hemorrhagic Fever Incidence In West Sumba Regency - Agustine, Uly; Belarminus, Petrus; Ora, Anderias Tarawatu; Boa, Grasiana Florida (Jurnal EduHealth, 2024)
Dengue hemorrhagic fever, caused by the dengue virus and spread by the Aedes aegypti mosquito, is characterised by sudden fever lasting 2 to 7 days without a clear cause, weakness/lethargy, restlessness, heartburn, and skin bleeding in the form of petechiae, ecchymosis, or purpura. Sometimes nosebleeds, diarrhoea, bloody vomit, loss of consciousness, or shock Dengue fever was identified in West Sumba District, mainly in Dira Tana Village, Loli District, with 50 cases. This study examines West Sumba Regency's Dengue Hemorrhagic Fever incidence and home environmental variables. This quantitative case-control study compares Dengue Hemorrhagic Fever patients to controls. This quantitative case-control study compares Dengue Hemorrhagic Fever patients to controls.Statistical analysis with a significance value of 5% (0.05) yielded a p-value of 0.491, indicating no association between house shape or type and dengue illness. Because almost every respondent's house, both stilt and permanent, has waste water drainage channels, breeding places, resting places, and containers inside and outside the house, dengue fever incidence is unrelated to house type.